Open hearts on open mic nights - Mohd Azmyl, Md Yusof * (The Malaysian Insight, 2023)
LAST weekend, I played two different gigs – one at a venue at which I’ve been regularly plying my trade in Petaling Jaya, and another that I haven’t been to in Kuala Lumpur since they changed management.